Professor Andryi Gonka – organizer of Lviv university stomatological school at beginning of ХХ century - Hrynovets, V.; Petryshyn, O. (Actual Dentistry, 2018)
Resume. The advancement of medical science, in particular dentistry, raises issues concerning the regularities and trends of this development in the historical perspective. Individuals, who at certain time were directly involved in the choice of the development course, are of great interest and should be studied as a part of a historical heritage. University dental clinic for the specialization of dentists was established in the early 20th century in Lviv University at the Faculty of Medicine. The first head and organizer of the University Dental School was Dr. Andriy Gon’ka. The article highlights scientific curriculum vitae, discovered in archives and libraries, of Doctor, subsequently Professor of Lviv University, which definitely influenced the development of modern Ukrainian University Dental School of Danylo Halytsky Lviv National Medical University. Key words: Dr. Andriy Gon’ka, Lviv University Dental School, dental clinic of Lviv University in the early 20th century.